"Contagious Accountability": A Global Multisite Randomized Controlled Trial on the Effect of Police Body-Worn Cameras on Citizens' Complaints Against the Police. (February 2017) - Ariel, Barak; Sutherland, Alex; Henstock, Darren; Young, Josh; Drover, Paul; Sykes, Jayne; Megicks, Simon; Henderson, Ryan
The use of body-worn cameras (BWCs) by the police is rising. One proposed effect of BWCs is reducing complaints against police, which assumes that BWCs reduce officer noncompliance with procedures, improve suspects' demeanor, or both, leading to fewer complaints. We report results from a global, multisite randomized controlled trial on whether BWC use reduces citizens' complaints. Seven discrete tests ( N = 1, 847 officers), with police shifts as the unit of analysis ( N = 4, 264), were randomly assigned into treatment and control conditions. Using a prospective meta-analytic approach, we found a 93% before–after reduction in complaint incidence ( Z = −3.234; p < .001), but no significant differences between trial arms in the studies ( d = .053, SE = .11; 95% confidence interval [CI] = [−.163, .269]), and little between-site variation ( Q = 4.905; p = .428). We discuss these results in terms of an "observer effect" that influences both officers' and citizens' behavior and assess what we interpret as treatment diffusion between experimental and control conditions within the framework of "contagious accountability."